Nutritional Composition of Fruits Selected by Long-Tailed Macaques (Macaca fascicularis) in Kuala Selangor, Malaysia - Norazila Kassim; Kamarul Hambali; Aainaa Amir (Tropical Life Sciences Research, 2017)
Proximate analysis of twelve species of fruits commonly consumed by long-tailed macaques (Macaca fascicularis), i.e., Arenga pinnata, Areca catechu, Terminalia catappa, Elaeis guineensis, Lagerstroemia tomentosa, Mangifera indica, Cascabela thevetia, Muntingia calabura, Musa sp., Artocarpus heterophyllus, Ficus tinctoria ssp. gibbosa and Ficus microcarpa, was conducted with the specific objective to determine the nutritional composition of the foodstuffs of long-tailed macaques. The results showed the following order of nutrients: fibre, protein, fat and ash. Based on the results of the chemical analysis, the highest percentage of fibre content (52.7%), protein (9.9%), fat (77.2%) and ash (8.5%) were found in A. catechu, T. catappa, E. guineensis and C. thevetia, respectively. The nutrient composition of these twelve fruit species was found to differ (ANOVA test: crude protein, F (11,24) = 87.978, p < 0.05; crude fibre, F (11,24) = 28.886, p < 0.05; crude fat, F (11,24) = 2081.396, p < 0.05 and ash, F (11,24) = 41.011, p < 0.05). Fibre was found in the highest amount among the four types of nutrients studied. Here, A. catechu had the highest relative fibre content of all tested fruits, E. guineensis had the highest fat content, T. catappa had the highest protein content, and the total mineral content was highest in C. thevetia. Proximate analysis of twelve species of fruits commonly consumed by long-tailed macaques (Macaca fascicularis), i.e., Arenga pinnata, Areca catechu, Terminalia catappa, Elaeis guineensis, Lagerstroemia tomentosa, Mangifera indica, Cascabela thevetia, Muntingia calabura, Musa sp., Artocarpus heterophyllus, Ficus tinctoria ssp. gibbosa and Ficus microcarpa, was conducted with the specific objective to determine the nutritional composition of the foodstuffs of long-tailed macaques. The results showed the following order of nutrients: fibre, protein, fat and ash. Based on the results of the chemical analysis, the highest percentage of fibre content (52.7%), protein (9.9%), fat (77.2%) and ash (8.5%) were found in A. catechu, T. catappa, E. guineensis and C. thevetia, respectively. The nutrient composition of these twelve fruit species was found to differ (ANOVA test: crude protein, F (11,24) = 87.978, p < 0.05; crude fibre, F (11,24) = 28.886, p < 0.05; crude fat, F (11,24) = 2081.396, p < 0.05 and ash, F (11,24) = 41.011, p < 0.05). Fibre was found in the highest amount among the four types of nutrients studied. Here, A. catechu had the highest relative fibre content of all tested fruits, E. guineensis had the highest fat content, T. catappa had the highest protein content, and the total mineral content was highest in C. thevetia. Analisis proximat dua belas jenis buah-buahan yang biasa dimakan oleh kera ekor panjang seperti Arenga pinnata, Areca catechu, Terminalia catappa, Elaies guineensis, Lagerstroemia tomentosa, Mangifera indica, Cascabela thevetia, Muntingia calabura, Musa spp., Artocarpus heterophyllus, Ficus tinctonia ssp. gibbosa dan Ficus microcarpa telah dijalankan dengan objektif khusus untuk menentukan kandungan nutrien makanan kera ekor panjang. Hasil kajian menunjukkan susunan nutrien yang berikut; serat, protein, lemak dan abu. Berdasarkan keputusan daripada analisis kimia, peratusan tertinggi kandungan serat (52.7%), protein (9.9%), lemak (77.2%) dan abu (8.5%) terdapat dalam A. catechu, T. catappa, E. guineensis dan C. thevetia. Kandungan nutrient daripada dua belas jenis buah-buahan ini didapati berbeza antara satu sama lain (Analisis ANOVA: serat, F (11, 24) = 87.978, p < 0.05; fiber, F (11,24) = 28.886, p < 0.05; lemak, F (11,24) = 2081.396, p < 0.05 and abu, F (11,24) = 41.011, p < 0.05). Kandungan serat adalah yang paling tinggi di antara keempat-empat jenis nutrien yang dikaji. Maka, A. catechu mempunyai kandungan serat tertinggi di antara buah-buahan yang diuji, E. guineensis mempunyai kandungan lemak tertinggi, T. catappa mempunyai kandungan protein tertinggi dan kandungan mineral yang paling tinggi terdapat dalam C. thevetia.